PROTOTYPENTHEORIE UND THEORIE DES SEMANTISCHEN FELDES ALS MITTEL ZUR BESCHREIBUNG VON KATEGORIESTRUKTUR - STEFANIUK, MARCELA (Wydawnictwo Naukowe UAM, 2005)
The article discusses the applicability of prototype theory and the theoiy of semantic fields for the analysis of category structure. The analysed empirical material consisted of German lexemes denoting Headgear. The first part of the article compares the theoretical assumptions of both prototype and lexical field theories. A category analysed from the structural perspective is built of elements that are all equal to one another. They all posses the same set of features called archilexeme content. Thus there are no better and no worse members of such a category. As opposed to this the prototype theory assumes that a fundament and reference point of a given category is the prototype - the category's best example. All the remaining category members take the places within the category depending on their similarity to the prototype. Within this theory we can therefore speak of grades of membership as well as of grades of representability. The second part of the article discusses the means used for the realisation of the analysis as well as its results. To present the results in short: the position of a prototype takes the lexeme ,Jiut" (hat) and the whole category seems to consist of a few smaller ones included within the superior category. Thus the category structure seems to be in accordance with the assumptions of the prototype theory. The prototype as the best example was often used to create names for objects that the questioned did not know. The indirect relation between the name and the object of language extern reality found its confirmation in the question concerned with the objects features. It was not possible for people to name any features if they can not call the representation of the object. As a result many of the given words came out with no features whatsoever. The final conclusion coming out of the analysis is that the prototype theory is more proper a tool for describing the structure of natural categories whereas the structural principles' application can only be the artificial categories.
Keywords: Prototypentheorie; Sematischer Felder